Mengupas Kemiskinan di Provinsi Banten: Bagaimanakah Peran Faktor Kependudukan dan Ekonomi? - Dewi, Ine Ratna (Ecoplan, 2023)
This study aims to analyze the simultaneous and partial effects of population and economic factors on poverty in Banten Province for the 2011-2019 period. Population factors include population growth rate, population density, and sex ratio. Meanwhile, economic factors cover the open unemployment rate, HDI, and GRDP. With secondary data from the publication page of Statistics Indonesia in Banten Province, this research was conducted using a descriptive quantitative approach. To analyze the data, the study used panel data regression analysis. The econometric model was estimated using the Ridge Regression model to overcome the multicollinearity problem between variables in the study. The statistical test results showed that the variables of population growth rate, open unemployment rate, sex ratio, human development index, and GRDP were reported to simultaneously and significantly affect poverty in Banten Province during 2011-2019. Partially, several variables, such as population growth rate, open unemployment rate, and HDI each had a significant negative effect on poverty. Interestingly, other variables, like the sex ratio, had a significant positive effect on poverty. The variables of population density and Gross Regional Domestic Product (GRDP) did not affect poverty. This study indicated that to reduce poverty, the Banten Provincial government should focus on improving the quality of human resources. They should improve health, education, skills, and expertise. Thus, people can have the competence to compete and obtain better jobs, which in turn can increase their income and welfare. In this way, they are expected to get out of the poverty cycle.